1982
DOI: 10.1002/ajpa.1330580107
|View full text |Cite
|
Sign up to set email alerts
|

Tooth eruption and browridge formation

Abstract: One of the most reasonable hypotheses regarding the functional significance of the browridge is that the supraorbital torus forms in response to masticatory stress during development. Oyen, Walker, and Rice (1979) have recently proposed a model that tests this hypothesis: if browridges are functionally related to masticatory stresses on the cranial vault, then changes in the biomechanics of the masticatory system ought to be reflected by changes in the browridge. To test their model they attempted to relate bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

1983
1983
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 8 publications
0
20
1
Order By: Relevance
“…This may alternate with periods in which previously erupting teeth are in occlusion, chewing effort is stable, and the brow surfaces are smooth. However, Russell (1982) was unable to confirm these sequences on the Papio sample reported by Oyen et al (197913).…”
Section: The Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…This may alternate with periods in which previously erupting teeth are in occlusion, chewing effort is stable, and the brow surfaces are smooth. However, Russell (1982) was unable to confirm these sequences on the Papio sample reported by Oyen et al (197913).…”
Section: The Resultscontrasting
confidence: 65%
“…This also differs from the proposed association of VP with tooth eruption stages. Russell (1982) analyzes the surface texture of the frontal bones of juvenile and subadult (age estimates ranging from 3.5 to 18 years) Australian aboriginal crania exhumed in the vicinity of the Murray River. Most showed areas of variable extent (up to 51.4%) resembling the areolar surface often seen on immature macaque and baboon brow areas, and identified as primary vascular bone.…”
Section: The Resultsmentioning
confidence: 99%
“…When modelling the supraorbital region as a beam (cf. Oyen and Russell, 1982;Range1 et al, 1985;Russell, 1982Russell, , 1985Wolpoff, 1980), this loading regime causes the dorsal interorbital and dorsal orbital regions to experience tensile strains directed perpendicular to the midsagittal plane, while the principal compressive strains are directed anteroposteriorly, parallel to the midsagittal plane ( Fig. 5B).…”
Section: Fmwmentioning
confidence: 99%
“…Many workers have suggested that enlarged browridges are an adaptive response to counter bending of the browridges in the frontal plane (Oyen and Russell, 1982;Rangel et al, 1985;Russell, 1982Russell, ,1985Wolpoff, 1980). These same workers assert that it is the dorsal interorbital region that experiences the most intense bending stress, and moreover, that the most intense bending stresses occur during incision or anterior tooth loading, rather than during mastication or posterior tooth loading (e.g., Endo, 1966).…”
Section: Fmwmentioning
confidence: 99%
“…These authors present evidence that the appearance of this areolar, nonlamellar bone, variously identified as fine cancellous bone, woven bone, or bundle bone [Pritchard, 1972], tends to coincide with stages of active molar eruption, and thus may indicate that brow ridge formation represents a response to masticatory forces. However, Russell [1982] was unable to con firm this developmental correspondence. It is also to be noted that the areolar surface bone can be observed in other parts of the cranium of juvenile primates.…”
Section: Discussionmentioning
confidence: 99%